2016
DOI: 10.15376/biores.12.1.117-142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Artificial and Natural Weathering on the Moisture Dynamic of Wood

Abstract: Wood that is used in outdoor applications is frequently exposed to weathering and is thus prone to fungal degradation. Ways to prevent fungal degradation include keeping the wood dry. The majority of hydrophobic and wood modification systems have been tested only on freshly treated wood. Little information is available on how various woodbased materials perform after a certain period of weathering. To elucidate this question, 17 wood samples were tested from the following species: oak (Quercus), sweet chestnut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The results of the present study show the effects of weathering to be most pronounced at the surface, which is in agreement with the results by Žlahtič and Humar (2016) where it was shown that mainly the short-term water uptake increased due to weathering. In one-dimensional capillary absorption, such as in the floating test, the moisture uptake of porous materials is generally found to be proportional to the square root of the time, t 1/2 .…”
Section: Comparison Of Axially Matched Specimenssupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study show the effects of weathering to be most pronounced at the surface, which is in agreement with the results by Žlahtič and Humar (2016) where it was shown that mainly the short-term water uptake increased due to weathering. In one-dimensional capillary absorption, such as in the floating test, the moisture uptake of porous materials is generally found to be proportional to the square root of the time, t 1/2 .…”
Section: Comparison Of Axially Matched Specimenssupporting
confidence: 93%
“…Most of the photodegradation and checking occurs within weeks of exposure, but can continue for at least 6-12 months before developing to continuous slow erosion (Evans 2013;Evans et al 2008;Kalnins and Feist 1993). Žlahtič and Humar (2016) recently found a difference in moisture absorption between specimens that had been subjected to outdoor weathering for 9 months and for 18 months, respectively. However, these tests did not exclude the occurrence of effects stemming from staining fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the decreased moisture performance may be associated with fungal decay. Fungi open up new voids in the cell matrix, which results in better permeability [48]. One possible explanation for increased electrical conductivity (hence, increased MC) could be the consequence of fungal colonisation, due to the presence of electrolytes excreted by the fungi.…”
Section: Moisture Performance Of Deckingmentioning
confidence: 99%
“…Furthermore, the elemental composition of some wood species, Pinus rigida, Juglans nigra, and Fagus sylvatica, Citharexylum spinosum and Morus alba, changed after inoculation with Penicillium selerotigenum, Paecilomyces variotii, and Aspergillus niger (Mansour et al, 2015a;Salem, 2016). Other studies reported that the aging factors act synergistically to have a more prominent infl uence on less durable-wood compared to durable or preservativetreated wood (Žlahtič and Humar, 2017). Also, there is a strong correlation between the moisture content of the cell wall and the ability of microorganisms to degrade wood (Schmidt, 2006;Van Meel et al, 2011; Meyer and Brischke, 2015).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%